2015
DOI: 10.1111/ajad.12198
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of buprenorphine treatment of the prescription opioid dependent pain patient

Abstract: Buprenorphine is an effective tool when treating the opioid-dependent chronic pain patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…86,87 This hypothesis was reflected in several studies included in the present systematic review, which focused on participants with aberrant use but excluded those with OUD. 54,55 JAMA Network Open | Substance Use and Addiction…”
Section: Discussionmentioning
confidence: 99%
“…86,87 This hypothesis was reflected in several studies included in the present systematic review, which focused on participants with aberrant use but excluded those with OUD. 54,55 JAMA Network Open | Substance Use and Addiction…”
Section: Discussionmentioning
confidence: 99%
“…The decision to stop taking opioid painkillers was not a spontaneous request on the part of the patient but a decision she took when she realized that no physician would prescribe her such a high daily dose. In the literature, it has been shown that replacing opioid medication with a substitution treatment of buprenorphine and buprenorphine-naloxone is effective for chronic pain and offers patients a good degree of satisfaction [32, 33]. However, as buprenorphine is off-label and buprenorphine-naloxone was off-label in France at this time, these treatments should be proposed only after withdrawal has been shown to have failed.…”
Section: Discussionmentioning
confidence: 99%
“… 74 Patients with comorbid chronic pain and OUD have reported satisfaction with buprenorphine treatment. 75 Also, buprenorphine is not immunosuppressive, 76 , 77 does not negatively impact the hypothalamic-pituitary-adrenal pathway, 78–80 and may reduce anxiety and depression. 81–84 …”
Section: Benefit-risk Assessment Of Buprenorphine Vs Conventional Opioidsmentioning
confidence: 99%
“…74 Patients with comorbid chronic pain and OUD have reported satisfaction with buprenorphine treatment. 75 Also, buprenorphine is not immunosuppressive, 76,77 does not negatively impact the [78][79][80] and may reduce anxiety and depression. [81][82][83][84] Overall, the safety data and additional benefits of buprenorphine suggest that it has a lower risk of adverse events compared with conventional opioids, most notably with respiratory depression.…”
mentioning
confidence: 99%